2021
DOI: 10.3390/ijerph182010901
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among COVID-19 Prevention Practices, Risk Perception and Individual Characteristics: A Temporal Analysis

Abstract: The effectiveness of public health measures in containing an infectious disease largely depends on how the general public is taking the prevention practices in daily lives. Previous studies have shown that different risk perceptions and sociodemographic characteristics may lead to vastly different prevention behaviors. This paper applies a temporal perspective in examining the changing patterns of prevention practices over time and their dynamic relationships with the perceived risk towards COVID-19 and its in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Thirdly, people’s experiences in the first wave, the “new lifestyle” advocated by the government at the end of the first wave, and the two factors mentioned above provided people with the sense that the risk of spreading COVID-19 would decrease soon, even when the infection started spreading again. This is consistent with studies in various countries showing that the effectiveness of lockdowns and the degree of compliance with restrictions diminish with the passage of time [ 52 54 ]. This result was likely attributable to the previous observation that the levels of people’s anxiety and their preventive behaviors decrease as their perception of the seriousness and immediacy of the threat reduced [ 44 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thirdly, people’s experiences in the first wave, the “new lifestyle” advocated by the government at the end of the first wave, and the two factors mentioned above provided people with the sense that the risk of spreading COVID-19 would decrease soon, even when the infection started spreading again. This is consistent with studies in various countries showing that the effectiveness of lockdowns and the degree of compliance with restrictions diminish with the passage of time [ 52 54 ]. This result was likely attributable to the previous observation that the levels of people’s anxiety and their preventive behaviors decrease as their perception of the seriousness and immediacy of the threat reduced [ 44 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed the association between an increase in the number of new PCR positive cases and a decrease in people’s mobility [ 45 – 50 ], and that the government declaration is effective to lead people to stay home [ 51 ]. In addition, studies in various countries showed that the degree of compliance with restrictions diminished over time [ 52 54 ].…”
Section: Introductionmentioning
confidence: 99%